Clinical relevance and implications of HPV-induced neoplasia in different anatomical locations - Prigge, Elena-Sophie; Knebel Doeberitz, Magnus von; Reuschenbach, Miriam (Mutation research. Reviews in mutation research, 2016)
Human papillomaviruses (HPV) are widespread DNA viruses that can infect epithelial cells of the skin and mucosa. Most HPV infections remain clinically unapparent and clear spontaneously. In few cases, however, HPV infections persist and can cause benign and malignant neoplasms at different anatomic locations. Malignant HPV-induced neoplasms are caused by distinct types of HPV (oncogenic or high-risk (HR) HPV types) and present in the anogenital (anus, penis, uterine cervix, vagina and vulva) and head and neck (particularly oropharynx) region. In the anogenital region defined precancerous stages precede invasive cancer. In the head and neck region there is clear evidence only for the invasive stage of HPV-induced neoplasia. In early infection stages the HPV oncogenes (E6/E7) are under tight control in the basal and parabasal cell layers. In more advanced precancerous stages increased expression of the HPV oncogenes E6 and E7 occurs (transforming infection) that may result in transformation of these cells. The defined carcinogenesis in the anogenital tract enables cancer early detection, particularly at the uterine cervix where cytologic and molecular tests contribute to early diagnosis and treatment at a non-invasive stage. Up to now, the treatment of HPV-related precancerous stages (high-grade intraepithelial neoplasia) and cancer is not specifically targeting molecular characteristics of the virus. This article reviews the current state and new developments in epidemiology, prevention, diagnosis and treatment of HPV-associated neoplasia in various anatomic locations.